Characterization of III-V semiconductor materials using rocking curve simulations - Wei, Ya Fei. (2009)
A windows-based simulation program using Borland C++, named Dynamical Simulation of X-ray Rocking Curves (DSRC), has been developed to calculate high resolution rocking curves for epitaxial layer structures using the fundamental X-ray scattering equations of dynamical diffraction. A bottom-up approach has been used to calculate rocking curve reflectivities for multilayer structures, wherein, starting from the bottom of the substrate, where the reflectivity is assumed zero, it is possible to calculate the reflectivity at the top of the multilayer structure by solving Takagi-Taupin equations. For multilayer structures showing complicated rocking curves, a simulation of the rocking curve has been found to provide a more accurate interpretation by comparing with the corresponding experimental rocking curve. Initial data from experimental rocking curves are used to calculate rocking curves for the multilayer structure and then compared with experimental curves. The input data are slightly adjusted about their initial values until a reasonable fit with experimental curves is achieved. The initial data consist of the knowledge of the thickness and mismatch variations of each layer in the multilayer structure. An accurate interpretation of layer characteristics from such a simulated fit has thus been made possible.